2021
DOI: 10.3390/w13233472
|View full text |Cite
|
Sign up to set email alerts
|

Competition and Plant Trait Plasticity of Invasive (Wedelia trilobata) and Native Species (Wedelia chinensis, WC) under Nitrogen Enrichment and Flooding Condition

Abstract: Nitrogen (N) is the important nutrition that regulatory plant functioning and environmental stability of invasive plant species under flooding (F) conditions. Little information clarifies the role of nitrogen enrichment and flooding on the invasive plant functional traits and competition with native competitors. Plant functional traits play an essential role in the successful growth of plants under different environmental conditions. Therefore, greenhouse pots experiment was conducted with invasive plant speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Invasive plant species are a major threat to the native biodiversity [35]. People are trying to manage its growth by using different cultivation techniques, planting methods and fertilizers [5]. In the last ten years, a trend of using modern skills and technologies have emerged in the agriculture sector in order to develop a better understanding of the relationship among many processes occurring in nature.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Invasive plant species are a major threat to the native biodiversity [35]. People are trying to manage its growth by using different cultivation techniques, planting methods and fertilizers [5]. In the last ten years, a trend of using modern skills and technologies have emerged in the agriculture sector in order to develop a better understanding of the relationship among many processes occurring in nature.…”
Section: Resultsmentioning
confidence: 99%
“…W. trilobata is the terrestrial plant species, but it is also found in wetland areas. It indicated that some of its growth traits assist W. trilobata to grow in wetland conditions like plant height and leaf area [5]. In wetland conditions, flooding and nitrogen are the major environmental factors that disturb the growth of native plant species as compared with invasive plant species [10].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Approximately 17% of the Earth’s land surface is highly invaded, and it is predicted that the number of non-native vascular plants in temperate Asia will increase by 41% by 2050 [ 12 ]. Consequently, the current focus has shifted from safeguarding native species to managing alien species to protect and restore native biodiversity and ecosystem services [ 13 ]. While numerous studies have examined the direct impacts of invasive species, it is essential to recognise that their legacy effects continue to impact ecosystems long after they are removed.…”
Section: Introductionmentioning
confidence: 99%